БАЗОВЫЕ КАЧЕСТВА СОВРЕМЕННЫХ ПЕДАГОГИЧЕСКИХ ТЕХНОЛОГИЙ, ИСПОЛЬЗУЕМЫХ ПРИ ОБУЧЕНИИ РУССКОМУ ЯЗЫКУ - Толегенова, Г.Ж. (SCIENCE and SOCIETY, 2025)
The article analyzes modern pedagogical technologies used in teaching the Russian language, such as learner-centered education technologies aimed at activating and intensifying student activity. The authors conclude that in order to help students systematize the knowledge gained in the subject and improve or develop speech skills, teachers need to employ a variety of pedagogical technolodies.
Keywords: pedagogical technologies; Russian language; student; teacher; critical and creative thinkindg; knowledge; skills; abilities